Sistem Informasi Perwalian Adopsi MBKM di Polman Negeri Babel - Fitri, Salsabilah; Rissinta, Rissinta; Josi, Ahmat; Andriyanto, Sidhiq (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The guidance process and credit claims in Polman Negeri Babel are still carried out manually, where each guardian lecturer must retrieve and process student data without using an information system that makes the results inaccurate. Because of this, we build Website-based independent adoption guardianship information system for independent campus learning (MBKM). The result achieved is the use of a Website-based information system that can facilitate guidance and claim credits. The output which is produced in this system is a summary of the semester guidance results and reports at the guardian lecturers.